2003
DOI: 10.7863/jum.2003.22.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Pelvic Fluid in Asymptomatic Children

Abstract: Our data suggest that the presence of minimal pelvic fluid in children of all ages and both sexes is a physiologic finding and should be evaluated in the appropriate clinical context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 7 publications
1
17
1
Order By: Relevance
“…Rathaus et al evaluated intra-abdominal FF in 266 patients with acute and/or chronic abdominal pain versus 396 asymptomatic pediatric patients and reported a significantly higher rate of FF in children with abdominal pain (28.6%) as compared to asymptomatic children (7%). Gender did not affect the presence of FF in the present study, similar to results by Rathaus et al [16]. Patients that had FF in the Douglas and pelvic areas were also significantly younger while 85.4% of postmenopausal women did not have FF.…”
Section: Discussionsupporting
confidence: 91%
“…Rathaus et al evaluated intra-abdominal FF in 266 patients with acute and/or chronic abdominal pain versus 396 asymptomatic pediatric patients and reported a significantly higher rate of FF in children with abdominal pain (28.6%) as compared to asymptomatic children (7%). Gender did not affect the presence of FF in the present study, similar to results by Rathaus et al [16]. Patients that had FF in the Douglas and pelvic areas were also significantly younger while 85.4% of postmenopausal women did not have FF.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of free intraperitoneal fluid may be a cardinal sign of an acute inflammatory process in a patient with abdominal pain in a nontraumatic setting. Small amounts of free fluid have been found on diagnostic imaging and are considered physiologic in asymptomatic children 1 , 2 . Although a finding of free intraperitoneal fluid among children with blunt abdominal trauma may signal an associated solid or hollow viscous injury, recent studies have suggested that isolated free intraperitoneal fluid detected on diagnostic imaging in pediatric trauma patients, with no associated findings of solid‐organ injury, a normal mental status, and lack of abdominal tenderness, may be managed conservatively without surgery 3 5 .…”
mentioning
confidence: 99%
“…In previous studies, prevalence of fluid in asymptomatic children with a few comorbidities during their visits was approximately 12% [13]. In this study, the prevalence of fluid within both female (91%) and male (67%) groups was much higher.…”
Section: Discussionmentioning
confidence: 43%
“…However, detection of minimal PFF in healthy children is not uncommon, possibly due to increased peritoneal permeability [1, 2]. Previous studies using ultrasonography have indicated a higher prevalence (12 %) of PFF in asymptomatic children aged 9 to 15 years compared to other age groups, with the maximum volume ranging from 1 – 6.9 mL [13]. While ultrasonography remains the most readily available modality for evaluation of PFF, the sensitivity for detection of free pelvic fluid is greatly improved with MRI.…”
Section: Introductionmentioning
confidence: 99%